Associação entre os sistemas histo-sanguíneos ABO, Secretor e Lewis e as formas clínicas da Doença de Chagas - Bernardo, Cássia Rubia (2014)
Introduction: Chagas disease is caused by the protozoan Trypanosoma cruzi, which is transmitted to humans commonly in the feces of a hemipterous popularly known as barber. The natural infection occurs mainly in childhood. After a period of approximately two decades infected individuals develop clinical manifestations such as Chagas heart disease and Chagas gastrointestinal disease (Megaesophagus and/or Megacolon). The expression of the antigens belonging to histo-blood systems ABO, Secretor and Lewis, controlled by the genes ABO (9q34.1), FUT2 (19q13.3) and FUT3 (19p13.3) differs between the organs affected by Chagas disease. It is possible that the differential tissue expression of ABO, Secretor and Lewis histo-blood groups influences the clinical manifestations of Chagas disease. Aim: The aim if this study was to verify if the antigens of the histo-blood systems ABO, Secretor and Lewis are associated with different clinical forms of Chagas disease. Materials and methods: After obtaining the informed consent peripheral blood and serum samples from 827 individuals were collected. Patients were divided into three subgroups according to their clinical state (megacólon [n=66], megaesophagus [n=119] and cardiomyopathy [n=154]). The control group consisted of 488 blood donors properly fit for the donation. The Lewis and ABO phenotyping were performed by hemagglutination test tube and gel columns agglutination, respectively. The IgG anti-T. cruzi antibodies were identified by ELISA. FUT2 and FUT3 genotyping were carried out by PCR-RFLP. Results: The mean age of patients with Chagas disease was 64.8±11.2 and blood donors 34.3±11.0 (p<0.0001). The differences between the percentages of the sex of the patients and donors were statistically significant (p <0.0001). The frequencies of ABO, Secretor and Lewis distributed in the three forms of the disease compared with each other and with donors, did not give differences statistically significant. The comparison between the ABO and Secretor combined, according to the three forms of Chagas disease, showed statistically significant differences for megaesophagus form (p=0.015). The frequencies of ABO, Secretor and Lewis antigen profiles between patients and donors showed differences statistically significant in favor of BLeb antigen (p=0.032). Conclusion: The results suggest that the high expression of antigen B, which characterizes the B and AB blood groups under the control of functional FUT2 (Secretor) gene acts as a risk factor for megaesophagus form of the Chagas disease.